ANALYSIS OF EDUCATIONAL FINANCING AT SMA GOTONG ROYONG IN KOTA BANGUN - Saparuddin, Muhammad; Mulawarman, Mike Gede; Warman, Warman; Haryaka, Usfandy (Borneo Journal of Primary Education, 2024)
This study aims to analyze the structure, allocation, and management of educational financing at SMA Gotong Royong in Kota Bangun. The focus of this research is to understand how the school allocates its budget for various needs such as operational expenses, maintenance, and capital, as well as to identify the challenges faced in financial management. The research approach used is descriptive qualitative, which allows for an in-depth analysis of school financing data, budget allocation, and the effectiveness of its usage. The findings of the study reveal that the largest allocation of SMA Gotong Royong's budget is directed toward Personnel Expenditures, which account for 81.52% of the total budget of IDR 72,128,000. This reflects the school's priority on regular staff honorarium payments. However, the dominance of personnel expenditures also presents challenges, such as limited funds for long-term investments like facility procurement and infrastructure improvement. Capital Expenditures, which only account for 4.62%, were used for the purchase of a portable scanner, but this is far from sufficient to meet the optimal needs for supporting technology development and modern learning facilities. The distribution of the budget across quarters shows an uneven pattern. The first and third quarters have the highest allocations, amounting to IDR 18,032,000 and IDR 21,332,000, respectively, while the second quarter is relatively lower as it only covers routine staff payments. Maintenance Expenditures received an allocation of 9.24%, which was focused on the upkeep of the UKS room and water storage. However, this allocation needs to be expanded to include the improvement of other facilities, such as classrooms and laboratory equipment. The conclusion of this study emphasizes the importance of increasing the allocation for Capital Expenditures to support sustainable long-term investments. Furthermore, a more balanced distribution of the budget across each quarter should be prioritized to ensure effective financial management. The findings of this study are expected to serve as a reference for other private schools in formulating effective financing strategies and provide input to policymakers to support private schools in providing high-quality and sustainable education.